Applying of Number Printing in Fun Cooking Activity to Improve Cognitive Ability of 4 to 5 Years Children at RA Al Huda Jember - Laily Nur Aisiyah; Senny Weyara Dinda Saputri (The Faculty of Teacher Training and Education The University of Jember Jember, Indonesia, 2022)
Cognitive development is an important aspect, where cognitive processes are related to the level of intelligence (intelligence). This ability needs to be developed in early childhood so that they can understand the various symbols that exist around their environment and solve simple problems that occur. Cognitive development in early childhood can be applied through playing while learning activities through which the ability to recognize, remember, think convergently, diverge, assess, and observe shapes, colors, sizes and see similarities and differences. Cooking is a powerful teaching activity that can be used as an integral part of an early childhood curriculum. In cooking activity there is playing symbols supports children's cognitive development. RA Al-Huda Jember found problems related to the ability of children to recognize symbols of numbers (numbers) and letters. In general, children aged 4-5 years have difficulty distinguishing symbols of numbers 1-10 and distinguishing letters from one another, especially those that have almost the same shape. In this study, children stimulated by playing symbols through activities to print numbers in fun cooking activities to improve children's cognitive abilities. This study used pre experimental designs with One-group pre-test and post-test designs. This study compares the results of the pre-test before treatment and post-test after treatment. Applying of number printing in fun cooking activity can improve cognitive ability of 4 to 5 years children at RA Al-Huda Jember to name the symbols for the numbers 1-10, use the symbols for numbers to count, and match the numbers and the symbols.